Implementasi Kriptografi Advanced Encryption Standard dan Least Significant Bit untuk Keamanan Pesan Email dalam Gambar - Sidiq, Repi Fahmi; Rahayu, Raden Erwin Gunadhi; Supriatna, Asep Deddy (Institut Teknologi Garut, 2023)
Email is one of the most common ways to communicate and exchange information inside and outside the office. The manager of the Garut Post office always holds meetings and visits outside the city so that the manager is not always in his office. At the Garut Post office there are several employees based on their level, such as permanent employees and interns. In making payroll, permanent employees do not need to communicate with the manager because it is already listed at the Garut Post office. However, interns must communicate with their manager, so this is often done by sending email messages. Based on the results of interviews conducted with the manager of the Garut Post office, according to him, messages via email are not always safe in sending personal and confidential information. According to a study, 85% of all cyber attacks that occur on companies are caused by phishing attacks via email. Phishing attacks are the most common technique used by hackers to steal sensitive information from email users. The Garut Post Office needs to have a Website-Based Application for Securing Email Messages in Images Using Advanced Encryption Standard (AES) and Least Significant Bit (LSB), so that it can increase the level of security and privacy in sending and receiving email messages for Interns and Managers. The methodology is the Extrime Programming (XP) methodology, to encrypt email messages using AES for security, as well as inserting the encrypted message into an image using the LSB method so that it is not visible. In addition, this research wants to integrate this technique into the website interface, test its security effectiveness, and contribute to the field of information security.